Natural resources for dye-sensitized solar cells. Issue 12 (December 2021) - Kusumawati, Yuly; Hutama, Aulia S.; Wellia, Diana V.; Subagyo, Riki
Abstract: While the development of dye-sensitized solar cells (DSSCs) has been ongoing for more than 30 years, the currently obtained efficiency is unsatisfactory. However, the study of DSSC development has produced a fundamental understanding of cell performance and inspired other devices, such as perovskite cell solar cells. DSSCs consist of a dye-sensitized photoanode, a counter electrode, and a redox couple in the electrolyte system. Each of the components has an important role and cofunctions with each other to obtain a high power conversion efficiency. Various modifications to each DSSC component have been applied to improve their performance. Additionally, to generate improvements, the effort to reduce production costs has been crucial. The utilization of natural sources for DSSC components is a possible solution to this issue. The utilization of natural resources also aims to increase the value of the natural resource itself. In this review, the applications of various natural sources for DSSC components are described, as well as the modification efforts that have been made to enhance their performance. The discussion covers the utilization of natural dye for sensitizer dyes in liquid DSSC applications: (1) utilization of biopolymers for quasi-solid DSSC electrolytes, (2) green synthesis methods for photoanode semiconductors, and (3) development of natural carbon counter electrodes. The detailed factors that influence improvements in cell performance are also addressed. Abstract : Dye sensitized solar cells; Natural resources; Biopolymer; Natural counter electrode; Green synthesis.